How Does Proline Treatment Promote Salt Stress Tolerance During Crop Plant Development? - El Moukhtari, Ahmed; Cabassa-Hourton, Cécile; Farissi, Mohamed; Savouré, Arnould (Frontiers in Plant Science, 2020)
Soil salinity is one of the major abiotic stresses restricting the use of land for agriculture because it limits the growth and development of most crop plants. Improving productivity under these physiologically stressful conditions is a major scientific challenge, because salinity has different effects at different developmental stages in different crops. When supplied exogenously, proline has improved salt stress tolerance in various plant species. Under high-salt conditions, proline application enhances plant growth with increases in seed germination, biomass, photosynthesis, gas exchange and grain yield. These positive effects are mainly driven by better nutrient acquisition, water uptake and biological nitrogen fixation. Exogenous proline also alleviates salt stress by improving antioxidant activities, and reducing Na+ and Cl- uptake and translocation, while enhancing K+ assimilation by plants. However, which of these mechanisms operate at any one time varies according to the proline concentration, how it is applied, the plant species and the specific stress conditions as well as the developmental stage. To position salt stress tolerance studies in the context of a crop plant growing in the field, here we discuss the beneficial effects of exogenous proline on plants exposed to salt stress through well-known and more recently described examples in more than twenty crop species in order to appreciate both the diversity and commonality of the responses. Proposed mechanisms by which exogenous proline mitigates the detrimental effects of salt stress during crop plant growth are thus highlighted and critically assessed.